The analysis on capital asset pricing model (CAPM) on the Jakarta Islamic Index (JII) - Edi Susilo (NUsantara Islamic Economic Journal, 2023)
The purpose of this research is to analyze the use of the Capital Asset Pricing Model (CAPM), for investment decisions in the Jakarta Islamic Index (JII), the period June 2015 - November 2018. This research is a descriptive quantitative study. The object of this study is all stocks recorded on the Jakarta Islamic Index (JII), for the period June 2015 - November 2018. Sampling using purposive sampling technique, selected 19 stocks that were consistently recorded during the study period. The aftereffects of this investigation demonstrate that efficient stocks with individual returns higher than the expected rate of return [(Ri)> E (Ri)], are 9 stocks, namely ADRO, ASII, INCO, INDF, SMGR, TLKM, UNTR, UNVR and WSKT. . While stocks with individual returns lower than the expected rate of return [(Ri) <E (Ri)], or inefficient stocks are 10 stocks, namely; AKRA, BSDE, ICBP, KLBF, LPKR, LPPF, PGAS, PTPP, SMRA and WIKA. The best investment decision for investors is to buy stocks efficiently.